简体   繁体   中英

How to solve this recurrence relation: T(n) = T(n-1) * T(n-2)

Consider this recurrence relation:

T(n) = T(n-1) * T(n-2)    n>2
T(1) = 1, T(2) = 2

How i can solve it? And finally: T(n) = O(?)

I think we should take log of both sides or something like. But i have no idea to continue.

You start by taking the logarithm of both parts to get:

log(T(n)) = log(T(n-1)) + log(T(n-2))

Now you substitute it with log(T(n)) to K(n) so you have to solve the problem K(n) = K(n-1) + K(n-2) . Doing similar thing you will get the solution

K(n) = c1 * F(n) + c2 * L(n), where F(n) is a Fibonacci number and L(n) is a Lucas number and c1, c2 are just some constants. So now to get your answer you just have to revert the logarithm.

So your solution is e^(c1 * F(n) + c2 * L(n)) . Following my previous explanation the complexity of this is O(e^(phi^n))

The technical post webpages of this site follow the CC BY-SA 4.0 protocol. If you need to reprint, please indicate the site URL or the original address.Any question please contact:yoyou2525@163.com.

 
粤ICP备18138465号  © 2020-2024 STACKOOM.COM